2000
DOI: 10.1136/aim.18.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hot Flushes in Breast Cancer Patients with Acupuncture

Abstract: SummaryA common treatment for post-menopausal hot flushes is to raise oestrogen levels with hormone replacement therapy. However this option is not considered suitable for breast cancer patients with hormone sensitive carcinoma, since an increase in oestrogen is contraindicated. This leaves little available as an effective conventional therapy.There has been some evidence that acupuncture is a suitable treatment for hot flushes, so a series of 22 consecutive breast cancer patients referred by an oncologist for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Acupuncture has been used for the natural climacteric, [38][39][40][41][42] for patients having tamoxifen treatment for breast cancer, [42][43][44][45][46][47] and for patients with prostate cancer. Education and practice with superficial acupuncture.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture has been used for the natural climacteric, [38][39][40][41][42] for patients having tamoxifen treatment for breast cancer, [42][43][44][45][46][47] and for patients with prostate cancer. Education and practice with superficial acupuncture.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, acupuncture to a particular area has produced both local and distant effects, according to traditional terminology. [12][13][14][15][16][17][18][19][20][21][22] Another study demonstrated that acupuncture was effective in the treatment of patients with pain and limited ROM, when given within 14 days of breast cancer surgery with node axillary dissection. 18 In that study, however, additional acupuncture meridian points were used according to health conditions of the patients before and after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of lymphoedema was classified as 1 to 3, according to skin characteristics and limb consistency through palpation and visual inspection. 14 The absence of alterations was classified as 0 (zero).…”
Section: Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three prospective uncontrolled cohort studies have been completed, one in men who had undergone castration for prostate cancer, and two in women who were taking tamoxifen for breast cancer. All demonstrated a reduction in vasomotor symptoms [309][310][311] . Prolonged stimulation using semi-permanent studs or needles, especially at SP6 appears to be associated with more long-term relief of symptoms 270 .…”
Section: Acupuncturementioning
confidence: 99%